The GHEP-EMPOP collaboration on mtDNA population data-A new resource for forensic casework - Prieto, L.; Zimmermann, B.; Goios, A.; Rodriguez-Monge, A.; Paneto, G. G. [UNESP]; Alves, C.; Alonso, A.; Chin, Chung Man [UNESP]; Cardoso, S.; Lima, G.; Anjos, M. J.; Whittle, M. R.; et al. (Elsevier B.V., 2011)
Mitochondrial DNA (mtDNA) population data for forensic purposes are still scarce for some populations, which may limit the evaluation of forensic evidence especially when the rarity of a haplotype needs to be determined in a database search. In order to improve the collection of mtDNA lineages from the Iberian and South American subcontinents, we here report the results of a collaborative study involving nine laboratories from the Spanish and Portuguese Speaking Working Group of the International Society for Forensic Genetics (GHEP-ISFG) and EMPOP. The individual laboratories contributed population data that were generated throughout the past 10 years, but in the majority of cases have not been made available to the scientific community. A total of 1019 haplotypes from Iberia (Basque Country, 2 general Spanish populations, 2 North and 1 Central Portugal populations), and Latin America (3 populations from São Paulo) were collected, reviewed and harmonized according to defined EMPOP criteria. The majority of data ambiguities that were found during the reviewing process (41 in total) were transcription errors confirming that the documentation process is still the most error-prone stage in reporting mtDNA population data, especially when performed manually. This GHEP-EMPOP collaboration has significantly improved the quality of the individual mtDNA datasets and adds mtDNA population data as valuable resource to the EMPOP database (www.empop.org). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: mtDNA; Mitochondrial DNA; GHEP-ISFG; EMPOP; Population analyses; Forensic science